Analisis Klasifikasi Broken Home pada Anak Menggunakan Metode Naïve Bayes Classifier - Supiyandi Supiyandi; Almanna Hussein; Irwan Gunawan; William Lutfi Rahman Harjo; Supiyandi Supiyandi (UIN Sunan Kalijaga Yogyakarta, 2023)
Broken home is a term that defines a situation in a family where most people handle no harmony, happiness, or peace. The impact of a broken home on a depressed family on children who can experience mental, emotional, and behavioral changes that are uncontrolled and undirected. Therefore, a classification is needed to categorize a child in a family as a broken home or not. The classification process will apply the Naïve Bayes Classifier classification method by taking into account the factors that refer to the statement that a child is called a broken home. With this classification, it is hoped that it can help know what and how a broken home child can be called a broken home and with this classification, it is expected that parents can minimize broken homes in children in the future by paying attention to the determining factors.